Chiral Spin Liquid Ground State in YBaCo_{3}FeO_{7} - W. Schweika; M. Valldor; J. D. Reim; U. K. Rößler (Physical Review X, 2022)
A chiral spin liquid state is discovered in the highly frustrated, noncentrosymmetric swedenborgite compound YBaCo_{3}FeO_{7}, a layered kagome system of hexagonal symmetry, by advanced polarized neutron scattering from a single domain crystalline sample. The observed diffuse magnetic neutron scattering has an antisymmetric property that relates to its specific chirality, which consists of three cycloidal waves perpendicular to the c axis, forming an entity of cylindrical symmetry. Chirality and symmetry agree with relevant antisymmetric exchanges arising from broken spatial parity. Applying a Fourier analysis to the chiral interference pattern, with distinction between kagome sites and the connecting trigonal interlayer sites of threefold symmetry, the chiral spin correlation function is determined. Characteristic chiral waves originate from the trigonal sites and extend over several periods in the kagome planes. The chiral spin liquid is remarkably stable at low temperatures despite strong antiferromagnetic spin exchange. The observation raises a challenge, since the commonly accepted ground states in condensed matter either have crystalline long-range order or form a quantum liquid. We show that, within the classical theory of magnetic order, a disordered ground state may arise from chirality. The present scenario, with antisymmetric exchange acting as a frustrating gauge background that stabilizes local spin lumps, is similar to the avoided phase transition in coupled gauge and matter fields for subnuclear particles.